2004
DOI: 10.1186/1471-2164-5-70
|View full text |Cite
|
Sign up to set email alerts
|

cDNA array-CGH profiling identifies genomic alterations specific to stage and MYCN-amplification in neuroblastoma

Abstract: Background: Recurrent non-random genomic alterations are the hallmarks of cancer and the characterization of these imbalances is critical to our understanding of tumorigenesis and cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 32 publications
5
29
0
1
Order By: Relevance
“…On average, non-MYCNA primary tumors had more CNAs and a greater proportion of the genome comprised of CNAs than MYCNA primaries (Fig. 1C), which is consistent with prior studies (Chen et al, 2004;Mosse et al, 2007). Moreover, regardless of MYCN status, CNS metastases had more CNAs and a (Matthay et al, 2003) 16 10 (63) 6 (37) All Pre-CNS primaries 27 14 (52) 13 (48) greater proportion of the genome comprised of CNAs, when compared with pre-CNS primaries (Fig.…”
Section: Cnas In Neuroblastoma Cns Metastases and Pre-cns Primariessupporting
confidence: 91%
“…On average, non-MYCNA primary tumors had more CNAs and a greater proportion of the genome comprised of CNAs than MYCNA primaries (Fig. 1C), which is consistent with prior studies (Chen et al, 2004;Mosse et al, 2007). Moreover, regardless of MYCN status, CNS metastases had more CNAs and a (Matthay et al, 2003) 16 10 (63) 6 (37) All Pre-CNS primaries 27 14 (52) 13 (48) greater proportion of the genome comprised of CNAs, when compared with pre-CNS primaries (Fig.…”
Section: Cnas In Neuroblastoma Cns Metastases and Pre-cns Primariessupporting
confidence: 91%
“…There are other examples in the literature of neuroblastoma cell lines and tumors with very similar amplified regions at 11q13 [11,25] or 12q13–q15 [11,21,30], respectively, and in two tumors synchronous amplification on both chromosomes have been reported [11,31,32], as in the present case. CCND1 , IGHMBP2 , ORAOV1 , FGF4 on chromosome 11q13, and CDK4 and MDM2 on 12q13-15 are interesting oncogenes in this context.…”
Section: Discussionsupporting
confidence: 79%
“…However, those 11q13 amplified neuroblastomas which also displayed MNA were diagnosed at earlier ages [11]. Clinical information on 12q amplified neuroblastoma is sparse in the literature but indicates advanced disease [30,33,34]. MNA may occur also in 12q amplified neuroblastoma [21,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent amplifications concern ALK amplification at band 2p23, frequently co-amplified with MYCN , accounting for 4% of NBs studied in a meta-analysis [33][35], found in five cases in our study (group 2) and ODC1 amplification at band 2p25 always found co-amplified with MYCN (20% of cases analysed in 2 studies) [9], [30], found in three cases in our study (group 2). Somatic amplification at 12q13–15 locus has also been described [6], [9], [12], [14][16], [19], [36]. This amplified region contains two potential target genes: CDK4 (12q13_14) involved in cell cycle progression and MDM2 (12q15), a target gene of the transcription factor tumour protein p53 and the encoded protein can target p53 for proteasomal degradation.…”
Section: Discussionmentioning
confidence: 98%